2011
DOI: 10.1096/fj.11-190223
|View full text |Cite
|
Sign up to set email alerts
|

Native α6β4∗ nicotinic receptors control exocytosis in human chromaffin cells of the adrenal gland

Abstract: In the present study, we have electrophysiologically characterized native nicotinic acetylcholine receptors (nAChRs) in human chromaffin cells of the adrenal gland as well as their contribution to the exocytotic process. α-Conotoxin AuIB blocked by 14 ± 1% the acetylcholine (ACh)-induced nicotinic current. α-Conotoxin MII (α-Ctx MII) exhibited an almost full blockade of the nicotinic current at nanomolar concentrations (IC(50)=21.6 nM). The α6*-preferring α-Ctx MII mutant analogs, α-Ctx MII[H9A,L15A] and α-Ctx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 64 publications
3
38
2
Order By: Relevance
“…In Pérez-Alvarez et al (2012b), evidence for the of a6b4* nAChRs was based on the observation that a-Ctxs selective for rat a6-containing nAChRs (McIntosh et al, 2004;Azam et al, 2008) inhibited the ACh-evoked currents in human adrenal chromaffin cells with similar IC 50 values. Additionally, the IC 50 value for the a3b4 nAChR antagonist a-Ctx AuIB was estimated to be .10 mM, which is inconsistent with the presence of a large population of a3b4 nAChRs based on the IC 50 value (750 nM) reported for rat a3b4 nAChRs (Luo et al, 1998).…”
Section: A-conotoxins Identify A3b4 Nachrs In Chromaffin Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Pérez-Alvarez et al (2012b), evidence for the of a6b4* nAChRs was based on the observation that a-Ctxs selective for rat a6-containing nAChRs (McIntosh et al, 2004;Azam et al, 2008) inhibited the ACh-evoked currents in human adrenal chromaffin cells with similar IC 50 values. Additionally, the IC 50 value for the a3b4 nAChR antagonist a-Ctx AuIB was estimated to be .10 mM, which is inconsistent with the presence of a large population of a3b4 nAChRs based on the IC 50 value (750 nM) reported for rat a3b4 nAChRs (Luo et al, 1998).…”
Section: A-conotoxins Identify A3b4 Nachrs In Chromaffin Cellsmentioning
confidence: 99%
“…The influx of calcium ions through nAChRs and voltage-gated calcium channels facilitates the fusion of synaptic vesicles with the plasma membrane to promote the release of vesicular content (Mollard et al, 1995;Perez-Alvarez et al, 2012a). Rodent (Di Angelantonio et al, 2003;Gahring et al, 2014) and bovine (Campos-Caro et al, 1997;Criado et al, 1997) adrenal chromaffin cells have been reported to express a variety of nAChR subtypes, including a7, a3b4*, a3b2*, and a4b2*, whereas in primates the reported receptor subtype(s) has included a7 and a6b4* (Perez- Alvarez et al, 2012aAlvarez et al, , 2012bHernandez-Vivanco et al, 2014). Given the number of nicotinic compounds used clinically, it is critical to identify all of the subtypes expressed by human adrenal chromaffin cells and to assess their pharmacology.…”
Section: Introductionmentioning
confidence: 99%
“…We used rat and mouse ␣6/␣3 subunit chimeras to model the ␣6␤2 and ␣6␤4 ligand-binding domain because injection of nonchimeric ␣6 with ␤2 and ␤3 fails to reliably produce functional expression (Kuryatov et al, 2000;Dowell et al, 2003;Papke et al, 2005;Dash et al, 2011). However, comparison of data obtained from studies on heterologously expressed chimeric constructs of ␣6 with studies on native ␣6-containing nAChRs demonstrate that these chimeric constructs and native ␣6-containing nAChRs share a similar pharmacological profile (Bordia et al, 2007;Capelli et al, 2011;Pérez-Alvarez et al, 2012). With use of this strategy and through synthetic iteration of ␣-Ctx PeIA, we created a ligand that to our knowledge is the most selective ␣-Ctx to date for distinguishing between ␣6␤2␤3 and ␣6␤4 nAChRs.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive investigations have identified the ␣6␤2␤3 and ␣6␣4␤2␤3 subtypes localized on dopaminergic neurons in the substantia nigra and ventral tegmental area as key modulators of dopamine release in striatum and nucleus accumbens (7)(8)(9)(10)(11)(12)(13)(14)(15)(16), making the receptors interesting in connection with Parkinson disease and nicotine addiction (4,6,17). Although not having been subjected to the same meticulous exploration as ␣6␤2* receptors, ␣6␤4* nAChRs have recently been reported to regulate norepinephrine release in mouse hippocampus (18), to play a major role for exocytosis in human adrenal gland chro-* This work was supported by the Lundbeck Foundation, The Aase and Ejner maffin cells (19), and to be expressed in rat dorsal root ganglia (20).…”
mentioning
confidence: 99%